The effect of internal factors on performance of banks in Malaysia - Ibrahim, Ismail Abdul Rahman (Faculty of Business Management, 2017)
Banks are the primary place for people in making money transaction. There are banks in every country, showing the importance of banks. In a competitive environment, even banks will fight to be the best and chosen by everyone. One will tend to choose the most financially reliable bank. A bank’s reliability can be measured by its performance, that is through the performance in each year. One way to measure it is by using Return on Assets (ROA) as its proxy. The performance can be influenced by both internal and external factors. This paper is written to investigate the effect of internal factors on performance of banks in Malaysia. Several banks have been chosen and a period of time has been set in this study. Commercial banks has been chosen in this study as they are the largest player in banking system for the financial system. The results are based on analysis and tests that have been conducted using a software.Cost-to-income, capital adequacy and liquidity have shown a significant relationship with the performance of banks (ROA) in Malaysia.